Intravital longitudinal imaging of hepatic lipid droplet accumulation in a murine model for nonalcoholic fatty liver disease - Moon, Jieun; Kong, Eunji; Lee, Jingu; Jung, Jinjoo; Kim, Eunha; Park, Seung Bum; Kim, Pilhan (Biomedical Optics Express, 2020)
Nonalcoholic fatty liver disease (NAFLD) is a rapidly increasing chronic liver disorder worldwide accompanied by hepatic steatosis, inflammation, fibrosis, and severe liver failure. Unfortunately, an effective treatment strategy for NAFLD has not yet been established, which has been hampered by the limited understanding of the pathophysiological drivers for NAFLD. To examine the unknown cellular and molecular mechanisms in the pathogenesis of NAFLD, there is an increasing need for the direct in vivo observation of hepatic microenvironments over extended periods of time. In this work, using a custom-built intravital imaging system and a novel fluorescent lipid droplet labeling dye, Seoul-Fluor 44 (SF44), we established an intravital imaging method to visualize individual lipid droplets and microvasculature simultaneously in the liver of live mice in vivo. In addition, in the nonalcoholic steatosis and steatohepatitis mouse model induced by a methionine and choline-deficient diet, we longitudinally visualized and quantitatively analyzed the development of lipid droplets in hepatocytes and sinusoid at a subcellular resolution during the progression of NAFLD up to 21 days in vivo.
Keywords: Hepatic steatosis; Longitudinal imaging; Micro-vasculature; Microenvironments; Molecular mechanism; Non-alcoholic fatty liver disease; Pathophysiological; Subcellular resolution